EXPERIMENTAL STUDIES ON SHRIMP- GRACILLARIA POLYCULTURE SYSTEM Effects of Gracillaria Density on Shrimp Sizes, Production, Survival And Growth Rate - Munifatul Izati; N.R Nganro; N Widyorini (JOURNAL OF COASTAL DEVELOPMENT, 2001)
This experiments was conducted as response to the serious negative impact of shrimp aquacultres into the environment. The shrimp-Gracillaria polyculture system was hypothesized to reduce excess pollutant in the shrimp pond. Variation in Gracillaria density was used as treatments. Two important aspects are discussed in this paper, that are the effect on shrimp productivity and efficiency in carbon energy conversion into harvestable products. There were significant evidences that the shrimp-Gracllaria polyculture system increase the sizes, total biomass, survival and growth rate of shrimp. The density of Gracillaria was positively correlated with all of those parameters. The carbon energy conversion was also significantly affected by Gracillaria density. The carbon energy conversion into harvestable products was more efficient if Gracillaria density was increased.